Conjugate photoelectron recapture peaks in the high resolution Auger electron spectra following near-threshold Ar 2p photoionization. (27th May 2020) - Kosugi, S; Martins, J; Hosseini, F; Marchenko, T; Travnikova, O; Bozek, J D; Ito, K; Sokell, E; Piancastelli, M N; Simon, M; Koike, F; Azuma, Y
Abstract: We have observed formation of Rydberg series superimposed on the Ar ( L 3 M 2, 3 M 2, 3 ) Auger electron spectral profile with photoexcitation just above the 2p −1 3/2 photoionization threshold. This is due to the recapture of photoelectrons induced by post-collision interaction between the Auger electron and photoelectron: Ar + 2p −1 3/2 + e − → Ar + 3p −2 ml + e − . The intensity distribution of the angular momentum state resolved Rydberg peaks revealed prominent conjugate peaks due to angular momentum exchange between photoelectrons and Auger electrons in the process. In addition, we measured the 2p −1 3/2 nl → 3p −2 ml + e − resonant Auger spectra with high resolution below the 2p −1 3/2 threshold. Our results showed that conjugate shake-up/down 2p −1 3/2 n d → 3p −2 m p + e − processes are stronger than the direct 2p −1 3/2 n d → 3p −2 m s, ( m −1)d + e − processes in the spectator Auger processes, implying a strong angular momentum exchange effect between photoelectron and Auger electron.